EFFECT OF LAND DEGRADATION DEGREE ON THE LAND COVER TYPE USING GIS TECHNOLOGY IN THE WEST OF BAGHDAD /IRAQ - Najeeb, Ahmed; Mahmood, Faleh (Iraqi Journal of Science, 2024)
In this study is the phenomenon of desertification risk assessment in the Abu Ghraibarea west of Baghdad / Iraq, which has an area of about (384.168 km 2), that the annualmean temperature is more than (22 C °). Rainfall was low, ranging from the (200 mm)per year for Iraq and (2.82) mm per year of the study area * temperature is high andevaporation is also high (mm 7.73) per year *, so the climate in general of the dry typeand the system of soil moisture is the kind of Aridic ( Torric). To this study was toidentify three indicators to monitor for the period from 2001 - 2005 using GIS and theseindicators are (soil, groundwater and the nature of land use), using ArcGIS 9.1. Theresults showed that the risk of desertification was part of the level observed in three outof five and the other areas are also within the level significantly, but to a lesser extent, itis possible to enter the top level if no aids by the authorities responsible for combatingdesertification and land degradation.*This data is the annual rate for the period (2001 to 2005).